Laser clad and HVOF sprayed Stellite 6 coating in chlorine rich environment with KCI at 700 °C - Pala, Zdenek; Bai, Mingwen; Lukac, Frantisek; Hussain, Tanvir (Springer, 2017)
Laser clads and HVOF coatings from a stellite 6 alloy (Co–Cr–W–C alloy) on 304 stainless steel substrates were exposed both bare and with KCl deposits in 500 ppm HCl with 5% O2 for 250 h at 700 C. SEM/EDX and PXRD analyses with Rietveld refinement were used for assessment of the attack and for analysis of the scales. The bare samples suffered from scale spallation and the scale was mostly composed of Cr2O3, CoCr2O4 and CoO, although due to dilution haematite (Fe2O3) was detected in the scale formed on the laser clad sample. A small amount of hydrated HCl was detected in bare samples. While the corrosion of the bare surfaces was limited to comparatively shallow depths and manifested by g and M7C3 carbide formation, the presence of KCl on the surface led to severe Cr depletion from the HVOF coating (to 1 wt%). Both inward and outward diffusion of elements occurred in the HVOF coating resulting in Kirdendall voids at the coating–steel interface. The laser clad sample performed significantly better in conditions of the KCl deposit-induced corrosion. In addition to the oxides, CoCl2 was detected in the HVOF sample and K3CrO4 was detected in the laser clad sample. Thermodynamic calculations and kinetic simulations were carried out to interpret the oxidation and diffusion behaviours of coatings.